2021
DOI: 10.3389/fmicb.2021.711137
|View full text |Cite
|
Sign up to set email alerts
|

The Gut Microbiome and Sex Hormone-Related Diseases

Abstract: The role of the gut microbiome has been a hot topic in recent years. One aim of this review is to shed light on the crosstalk between sex hormones and the gut microbiome. Researchers have observed a sex bias of the composition of the gut microbiome in mice and have proved that sex differences influence the composition of the gut microbiome, although the influence is usually obscured by genetic variations. Via cell studies, animal studies and some observational studies in humans, researchers have confirmed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(54 citation statements)
references
References 79 publications
3
41
0
1
Order By: Relevance
“…Our analyses of nasopharyngeal taxonomic composition at the phylum level revealed the existence of sex-associated differences within the age groups including individuals between 21 and 70 years of age, but not in the youngest and oldest people. As previously mentioned for the alpha diversity results, multiple sex-associated differences in taxonomic composition have also been described for the human gut microbiome 36 , and numerous studies have found evidence to support the idea that levels of sex hormones, such as progesterone 38 , androgen 39 , and oestrogen 40 , regulate its composition 41,42 . The effects of sex hormones on other microbial niches, such as the human vaginal microbiota, have also recently been demonstrated 43 .…”
Section: Discussionsupporting
confidence: 53%
“…Our analyses of nasopharyngeal taxonomic composition at the phylum level revealed the existence of sex-associated differences within the age groups including individuals between 21 and 70 years of age, but not in the youngest and oldest people. As previously mentioned for the alpha diversity results, multiple sex-associated differences in taxonomic composition have also been described for the human gut microbiome 36 , and numerous studies have found evidence to support the idea that levels of sex hormones, such as progesterone 38 , androgen 39 , and oestrogen 40 , regulate its composition 41,42 . The effects of sex hormones on other microbial niches, such as the human vaginal microbiota, have also recently been demonstrated 43 .…”
Section: Discussionsupporting
confidence: 53%
“…In turn, the microbial population affects SH levels to condition the host physiology and pathophysiology [62]. Such reciprocal GM/SH relationship is involved in the gender-related response to noxious stimuli and could partly explain the gender difference observed in the incidence and progression of certain diseases, including metabolic and CV disease [63]. An intriguing example of how SH and GM interact in the evolution of type-1 diabetes (T1D) derives from investigation on mouse models of non-obese T1D.…”
Section: Sex Difference and Gm Diversity: Bidirectional Cross Talk Be...mentioning
confidence: 99%
“…Just as GM is influenced by SH, in turn GM may be an important regulator of circulating levels of SH and SH metabolites [63]. In fact, GM is able to produce hormones (e.g., serotonin, dopamine, somatostatine), and to regulate the host's hormones homeostasis by inhibiting gene transcription (e.g., prolactin) or fostering conversion reactions (e.g., glucocorticoids to androgens) [58].…”
Section: Gm Composition Regulates Sex Hormone Levelsmentioning
confidence: 99%
“…Compared to other microbiomes found throughout the body, the urinary microbiome has not yet been adequately defined [ 24 ]. The few clinical trials that have been conducted typically suffer from constraints such as small sample size, imprecise method of urine collection, and high heterogeneity in characteristics such as race and age [ 25 ]. Defining a single general set of bacteria that constitutes a healthy bladder is thus challenging, but comparative studies have shed some light on overlapping and diverging urinary microbiome compositions.…”
Section: Urinary Microbiome In Healthy Individualsmentioning
confidence: 99%